Financial Ratio’s Analysis to Assess Finance Performance of Rural Owned Enterprise by Dencarik Village Bina Usaha Mandiri Buleleng Regency - Luh Sutarmi; I Wayan Karmana; Ni Made Wirasyanti Dwi Pratiwi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Rural Owned Enterprises are legal entities established by the village or built together with the village to manage the business, utilize the assets, develop the investment and productivity, provide services or other types of business for village community’s welfare. One of them is Rural Owned Enterprise by Dencarik Village Bina Usaha Mandiri. During the last three years, in 2019, 2020 and 2021, the net profit of Rural Owned Enterprises has decreased significantly. The decrease of the profit certainly has an impact on village’s income. The purpose of this study was aimed to determine the financial performance of Rural Owned Enterprises Bina Usaha Mandiri based on financial ratios. This research categorized as descriptive qualitative research to describe the company's financial performance by using analysis of liquidity ratios, profit- ability, solvency and activity. The results of financial ratios’ calculations were assessed with the standard assessment of the Regulation of the Minister of Koperasi and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006 about the Koperasi Award. Rural Owned Enterprises of Dencarik Bina Usaha Mandiri in 2019 received 53.6 for the assessment, in 2020 it received 46.4, and it got 42.9 in assessment in 2022. All of those scores were categorized as the poor category. With these findings, it indicated that it was necessary to make many improvements to Rural Owned Enterprises of Dencarik Village, Bina Usaha Mandiri to improve future performance.